Karakteristik Marshmallow Carica (Carica pubescens L.) dan Sari Wortel (Daucus carrota L.) dengan Perlakuan Penambahan Gelatin dan Putih Telur - Monicha Raeatya; Rosida Rosida (Universitas Islam Raden Rahmat, Malang, 2024)
This research aims to determine the effect of the addition gelatin and the addition egg white on the characteristics of marshmallows. The method used was a completely randomized design (CRD) with two factors. The first factor was the addition of gelatin (8%, 10%, 12%) and the second factor was the addition of egg white (6%, 8%, 10%). The results showed that the addition of gelatin and egg white had an effect on water content, ash content and hardness, but had no effect on antioxidant activity, vitamin C and reducing sugars. The best research results were marshmallows with the addition of 12% gelatin and the addition of 10% egg white which produced marshmallow characteristics with a water content of 19,98%, ash content of 0,23%, antioxidant activity of 29,64%, vitamin C of 13,10mg/100ml, reducing sugar 8,36%, hardness 1,06 N and organoleptic test showed color 3,76; taste 4,20; aroma 3,60; and texture 4,04.